2018
DOI: 10.1016/j.aop.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of minimal length uncertainty on the mass–radius relation of white dwarfs

Abstract: Generalized uncertainty relation that carries the imprint of quantum gravity introduces a minimal length scale into the description of space-time. It effectively changes the invariant measure of the phase space through a factor (1+βp 2 ) −3 so that the equation of state for an electron gas undergoes a significant modification from the ideal case. It has been shown in the literature (Rashidi 2016) that the ideal Chandrasekhar limit ceases to exist when the modified equation of state due to the generalized uncer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…The ultra-relativistic curve does not yield the Chandrasekhar limit: while the curve R(M ) tends to the original line M = M Ch as M → M + Ch , it is no longer bounded above when M increases. This means that white dwarfs can in principle gets arbitrarily large (for any M , there exists a nonzero R that satisfies the equilibrium equation between degenerate pressure and gravity; this is true for non-relativistic case too), consistent with the previous results obtained in [19] using a more rigorous method (see also [20][21][22]). In Fig.…”
Section: Generalized Uncertainty Principle and White Dwarfssupporting
confidence: 87%
“…The ultra-relativistic curve does not yield the Chandrasekhar limit: while the curve R(M ) tends to the original line M = M Ch as M → M + Ch , it is no longer bounded above when M increases. This means that white dwarfs can in principle gets arbitrarily large (for any M , there exists a nonzero R that satisfies the equilibrium equation between degenerate pressure and gravity; this is true for non-relativistic case too), consistent with the previous results obtained in [19] using a more rigorous method (see also [20][21][22]). In Fig.…”
Section: Generalized Uncertainty Principle and White Dwarfssupporting
confidence: 87%
“…The behavior of P (ξ) is shown in Figure 1b. We see that momenta higher than ξ max , determined by the cutoff p max of the noncommutative dispersion relation (6), are forbidden and the curve does not go beyond this limit.…”
Section: A Modified Thermodynamic Behaviormentioning
confidence: 86%
“…It has not only been shown that the existence of a lower bound Δx 0 has an impact on the HUP but also on quantum mechanics in general, and the properties of atoms and molecules and their interactions in particular [58][59][60][61][62][63][64][65][66][67][68]. Needless to say that it also plays a role in astronomy and high energy physics [63,69].…”
Section: Generalized Uncertainty Principlementioning
confidence: 99%